2020
DOI: 10.3390/su12229335
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilizer Effects on Pea–Barley Intercrop Productivity Compared to Sole Crops in Denmark

Abstract: Cereal–legume intercropping increases the nitrogen (N) input from biological nitrogen fixation (BNF) and improves the exploitation of fertilizer and soil N, often leading to higher grain N content and higher productivity per unit land area compared to monocrops. Previous studies have found that these effects are more tangible under low soil and fertilizer N conditions compared to high N availability, and there is a need to assess the N uptake at critical crop development stages in order to time the N applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Nitrogen fertilizer increased biomass and hay yields for sole crops and their mixtures. Similar findings have been recorded in other researches [9]. Analysis has shown that nitrogen fertilizer has a pronounced effect on the biomass and hay yield of oats compared to field peas.…”
Section: Biomass and Hay Yieldssupporting
confidence: 91%
See 1 more Smart Citation
“…Nitrogen fertilizer increased biomass and hay yields for sole crops and their mixtures. Similar findings have been recorded in other researches [9]. Analysis has shown that nitrogen fertilizer has a pronounced effect on the biomass and hay yield of oats compared to field peas.…”
Section: Biomass and Hay Yieldssupporting
confidence: 91%
“…The most significant advantages of intercropping legumes and cereals or grasses are the increased yields compared to sole stands [4][5][6][7], and better and more balanced biomass quality regarding proteins and energy [8]. Intercropped species better utilize nitrogen and other nutrients from the soil [9,10], as well as soil moisture and solar radiation, while other research highlights the benefits on the soil microorganisms [11]. The research thus far mentions several other benefits and, in particular, nitrogen transfer from the roots of legumes to the roots of different cereals or grasses [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Pea appears to store less vacuolar NO 3 − than non-legume species and increasing this storage capacity may be a useful target for improving NUE, providing the crop with a reservoir of N to sustain short-term requirements for growth. In intercropping systems, for example pea with barley, there is evidence that NUE is improved relative to a single pea crop [ 77 ]. Like other legumes, pea should have less dependence on N uptake from soil, with an optional N supply fixed by nodules.…”
Section: Discussionmentioning
confidence: 99%
“…The oven-dried samples were put in small plastic bags after grinding. The study of N and P uptake are the most common among mineral elements 55 , 56 . Concentrations of N and P in the plant dry matter were determined after digestion with H 2 SO 4 and H 2 O 2 ; N concentration was measured according to the Kjeldahl method 20 , whereas P concentration was measured by the molybdenum-antimony anti-spectrophotometric method 16 .…”
Section: Methodsmentioning
confidence: 99%